Empowering SMEs innovation through intangible factors - Agus Syarip Hidayat; Wee Ching Pok (Journal of Innovation and Entrepreneurship)
Abstract Due to constrained resources, small and medium-sized enterprises (SMEs) often have a low capacity to innovate. While research has focused chiefly on empowering SMEs' innovation through tangible factors, this paper explores the contribution of intangible factors towards innovation under frugality conditions. We address this gap using data collected from Indonesian SME automobile component manufacturers. We employ the expanded CDM (Crepon Duguet Mairesse) model that divides innovation into three stages: effort, output, and productivity. The findings showed that in addition to common tangible factors, intangible factors contribute to all stages of innovation, though tangible factors appear to exert greater influence. The direct impact of product innovation on firm performance is moderated by tangible factors, whereas the indirect impact is moderated by intangible factors. By examining how intangible and tangible factors simultaneously empower SMEs’ innovation and hence firms’ performance, we significantly contribute to advancing the theory of frugal innovation, the competition and strategy theory, and the extended resource-based view (ERBV).